Travelling through a powder keg: War and Tourist Imaginary in Sarajevo - Patrick Naef (Via@)
The aim of this article is to examine the influence of a recent conflict on the production of tourist imaginaries linked to a place, more precisely to Sarajevo, the capital of Bosnia-Herzegovina. Both the city itself, as well as the whole Balkan region, have often been compared to a powder keg, notably in the media coverage of the conflict which set fire to the Balkans during the 1990s. In addition, certain films tend to create a romantic and orientalist image of this region, largely equating it with one of fire and blood. I will show that this vision, which is albeit simplistic and limited, tends to create, for some tourists, an imaginary, and even a certain fascination tinged with adventure. In this context, the places which have undergone the trauma of war or the sites which symbolize resistance are being exploited by local actors and included in the tourist landscape of the city and region little by little.